Синтез, противоопухолевая и антибактериальная активность новых производных дигидронафталина и дигидробензо [h]хиназолина - К. К. Айрапетян (ՀՀ ԳԱԱ հրատ.)
На базе 1-амино-3,3-диметил-3,4-дигидронафталин-2-карбонитрила синтезированы ацилпроизводные, которые циклизованы в 2-замещённые 5,5-диметил-5,6-дигидробензо [h]хиназолин-4(3H)-оны. Алкилированием последних получены N- и O-алкилированные продукты. Хлорированием 4-оксобензохиназолинов синтезированы 4-хлорпроизводные, исходя из кото-рых получены 4-амино- и 4-гидразинопроизводные. Конденсацией последнего с ортомуравьиным эфиром синтезирован 4,4-диметил-11-фенил-4,5-дигидробензо[h] [1,2,4]триазоло[4,3-c] хиназолин. Изучение биологических свойств синтезированных соединений показало, что некоторые из них проявляют антибактериальные и противоопухолевые свойства. 1-Ամինո-3, 3-դիմեթիլ-3,4-դիհիդրոնավթալին-2-կարբոնիտրիլի (ամինոնիտրիլ) հիման վրա սինթեզվել են ացիլածանցյալներ, որոնք ցիկլվել են 2-տեղակալված 5,5-դիմե-թիլ-5,6-դիհիդրոբենզո[h]խինազոլին-4(3H)-ոնների: Վերջինիս ալկիլումը հանգեցրել է կամ N-, կամ էլ O-ալկիլացված արգասիքների: 4-Օքսոբենզո[h] խինազոլինների քլորացմամբ սինթեզվել են 4-քլորածանցյալներ, որոնց հիման վրա ստացվել են 4-ամինո- և 4-հիդրազինոածանցյալներ, վերջինիս և օրթոմրջնաթթվական էսթերի կոնդենսմամբ սինթեզվել է 4,4-դիմեթիլ-11-ֆենիլ-4,5-դիհիդրոբենզո[h][1,2,4] տրիազոլո[4,3-c]խինազոլին: Սինթեզված միացությունների կենսաբանական հատկությունների ուսումնասիրությունը ցույց է տվել, որ որոշ միացություններ ցուցաբերում են հակաբակտերիալ և հակաուռուցքային հատկություններ: The interaction of 1-amino-3,3-dimethyl-3,4-dihydronaphthalene-2-carbonitrile with acid chlorides of carboxylic acids resulted in the synthesis of acyl derivatives, which in the presence of chloride hydrogen in absolute ethanol were cyclized to 2-substituted 5,5-dimethyl-5,6-dihydrobenzo [h] quinazolin-4(3H)-ones. The alkylation of the latter with alkyl halides (methyl iodide and ethyl iodide) in the presence of potassium hydroxide has been studied. In case of using methyl iodide as the alkylating agent, N-substituted products are obtained, while the use of ethyl iodide leads to the formation of an O-substituted product. By chlorination of 4-oxobenzoquinazolines 4-chloro-derivatives were synthesized. Only 4-chloro-5,5-dimethyl-2-phenyl-5,6-dihydrobenzo [h]quinazoline was isolated in its pure form, while 4-chloro-5,5-dimethyl-2-ethyl-5,6-dihydrobenzo[h] quinazoline and 2-benzyl-4-chloro-5,5-dimethyl-5,6-dihydrobenzo [h]quinazoline were used without further purification. The interaction of chloro derivatives with secondary cyclic amines yielded 2-substituted 4-amino derivatives. By condensation of 2-phenyl-4-chloro derivatives with an excess of anhydrous hydrazine a hydrazine derivative was synthesized, which was transferred into 4,4-dimethyl-11-phenyl-4,5-dihydrobenzo[h] [1,2,4] triazolo[4,3-c] quinazoline without additional purification by interaction with orthoformate. The antitumor activity of compounds has been studied based on the model of Ehrlich's ascites carcinoma. In the experiment, N-(2-cyano-3.3-dimethyl-3.4-dihydronaphthalen-1-yl)benzamide at a dose of 50 mg/kg inhibits tumor growth by 40%. The antibacterial properties of synthesized compounds have been studied by the method of "diffusion in agar" at a bacterial load of 20 mln microbial bodies per 1 ml of medium. It has been found out that most of the investigated compounds show weak or moderate activity in relation to test-objects.
Keywords: Chemistry; Science; Biochemistry; Organic Chemistry